A Study on Fuzzy Decision Problem of a Queueing System with Finite Capacity by LR Method - et. al., S. Vijaya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, LR method has been proposed to mathematical non-linear parametric programming approach for the queueing decision problem. Using LR method, the minimal expected total cost of a crisp queueing system with finite capacity using LR – type trapezoidal fuzzy numbers is calculated. LR method is simple, short and convenient compared to alpha-cut method. Numerical example is illustrated for comparison between alpha – cut method and LR method.